2021
DOI: 10.1002/ps.6620
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of heat exposure‐associated escape behaviors and HSP gene expression in bed bugs (Cimex lectularius L.)

Abstract: BACKGROUND: Heat can be effective for bed bug elimination. However, in some cases bed bugs survive heat treatments. The objectives of this study were to determine the behavioral responses of bed bugs to rising harborage temperatures (23.0-49.0 °C) and identify which heat shock protein (HSP) genes are expressed after heat exposure. First, a custom-made copper arena and harborage were used to determine the escape behaviors of six bed bug populations. Next, HSP gene expression responses of select populations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…The release of AP in live bed bugs but not in frozen dead bed bugs indicates that insects must be alive prior to heat exposure to emit high concentrations of AP. This nding is similar to experiments which showed that live earthworms release AP in response to electrical shock 53 , but dead earthworms do not 55 .…”
Section: Emission Of Alarm Pheromones In Response To Lethal and Sub-l...supporting
confidence: 88%
See 3 more Smart Citations
“…The release of AP in live bed bugs but not in frozen dead bed bugs indicates that insects must be alive prior to heat exposure to emit high concentrations of AP. This nding is similar to experiments which showed that live earthworms release AP in response to electrical shock 53 , but dead earthworms do not 55 .…”
Section: Emission Of Alarm Pheromones In Response To Lethal and Sub-l...supporting
confidence: 88%
“…Previous research has compared the heat repellency behavior of different bed bug populations when exposed to rising temperatures in their harborages 37 . These studies found that when bed bug hiding places are heated to 40 43 °C, they can ee and randomly locate unheated areas in close proximity 37 .…”
Section: Implications Of Bed Bug Alarm Pheromone Emission To Heat As ...mentioning
confidence: 99%
See 2 more Smart Citations
“…HSPs exist widely in insects and may play an important role in their heat adaptation, heat tolerance, and heat protection [ 10 , 11 ]. For instance, HSPs play important roles as molecular chaperones in promoting correct protein folding and preventing denatured protein aggregation [ 12 ]. Based on molecular weight and homology, HSPs constitute a supergene family that was divided into six families (small HSPs, HSP40, HSP60, HSP70, HSP90, and HSP100) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%